Annual Plan 1972-73 (Draft) Narrative Notes on Programmes - Planning Commission (Planning Commission, 1972)
Agricultural Production continues to play an important role in increasing the National wealth and per capita income besides providing the basic raw materials required for industrial production. It was proposed to aim at a growth rate of 5 per cent for food grains in order to realise the optimum level of production of 79.00 lakh tonnes of food grains at the end of the Fourth Plan. The level of production during 1970-71 was assessed at 70.30 lakh tonnes of which the production of rice was estimated at 53.03 lakh tonnes against the production of 45.32 lakh tonnes of rice achieved during 1969-70. During 1971-72. 73.00 lakh tonnes of food grains has been fixed as the targeted level of production. This includes anticipated production of 54.00 lakh tonnes of rice. During 1972-73, the total food grains production is expected to be fixed at 75.00 lakh tonnes as the target. The phasing of expenditure and inputs during the Fourth Plan has been programmed accordingly. The suggested Plan outlay for 1972 73 is Rs 632.70 lakhs under State Plan schemes and Rs 152.12 lakhs under Centrally sponsored schemes.
Tamil Nadu
Tamil Nadu